Age‐Specific Association Between Cumulative Blood Pressure Exposure and Atrial Fibrillation Risk in Adults - Yi Yan; Qian Liu; Zhaofen Wang; Haijuan Wang; Peng Chang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The association between cumulative blood pressure (BP) exposure and atrial fibrillation (AF) risk across different age groups remains unclear. Methods We analyzed 77 180 participants from the Kailuan Study who were free of AF and had complete BP data from 2006 to 2010. Time‐weighted average BP was calculated as the sum of each interval's mean BP multiplied by the corresponding time interval, divided by total exposure duration. Participants were divided into 4 groups by time‐weighted average BP quartile: quartiles 1 (reference), 2, 3, and 4. Results Among 77 180 participants, 57 344 were young and middle‐aged adults (aged <60 years), and 19 836 were older adults (aged ≥60 years). During a median follow‐up of 12 years, 746 (0.97%) participants developed AF, including 313 younger adults and 433 older adults. Higher time‐weighted average BP significantly increased AF risk, with stronger associations in younger adults. Compared with the quartile 1 group (time‐weighted average systolic BP <117.35 mm Hg), the quartile 4 group (time‐weighted average systolic BP ≥139.67 mm Hg) showed significantly higher AF risk, with a hazard ratio (HR) of 2.67 (95% CI, 1.87–3.81) in younger adults and 1.48 (95% CI, 1.04–2.11) in older adults. Elevated time‐weighted average diastolic BP (≥89.50 mm Hg) increased AF risk in younger adults (HR, 1.68 [95% CI, 1.19–2.38]) but not in older adults (HR, 1.27 [95% CI, 0.95–1.68]). Persistent hypertension exposure conferred higher AF risks in both age groups. Conclusions Elevated cumulative BP exposure increases AF risk in all age groups but poses a greater risk in younger adults. These findings highlight the need for age‐specific BP management strategies to prevent AF.